Peer Effects: We Talk a Lot, but We Know Little (Observatorio Económico, 2014)
Amid the intense debate over education reform, one of the concepts most frequently invoked lately by specialists, stakeholders, politicians, and journalists is the so-called “peer effect.” This article seeks to briefly review the scope of this concept and the empirical evidence available to date on the matter, which, as we will see, is much less than we would like. Continue reading...
Keywords: academic segregation; cultural capital; schools